(untitled) (ELang | An English Language Education Journal, 2025)
The research entitled "Enriching Students’ Vocabulary Mastery Through Spelling Bee Game". It was conducted in the first semester of the second grade of SMP BPPI Baleendah. The study used quasi experimental design with the treatment held in three meetings, and the total sample in this research was 50 students’ that were taken from two classes, VIII A and C. In collecting the data, were applied as the instruments, pre-test, post-test and questionnaire. From the test, it can be seen that with the df = N1+N2-2 = 50-2 = 48, at P- 0.05 of two tailed of significance, the critical value of t is 2.009. As the value of the derived t (to) exceeds or is higher than that of the critical value of t (4.505 > 2.009). Thus, Ho is rejected and Ha is accepted. This means that the use of Spelling Bee Game method to enrich students’ vocabulary mastery is effective. Furthermore, based on the questionnaire, the students’ response to the use of Spelling Bee Game method to enrich students’ vocabulary mastery is good and positive. All of the students’ found it easy to learn vocabulary and learn to spell after participating in the Spelling Bee Game method. Moreover, most of the students felt that the Spelling Bee Game method was a fun way to learn new words and a useful tool to improve vocabulary.